The social imaginary of study abroad: complexities and contradictions. Issue 3 (2nd July 2016) - Kubota, Ryuko
Abstract : Many universities around the world today are actively promoting study abroad to raise their international profiles. This trend is tied to the neoliberal social imaginary, which constructs study abroad as a tool for students to develop communication skills, a global mindset, intercultural competence and a competitive edge in global labour marketplaces. Such social imaginary is reflected in online descriptions of the imagined benefits that study abroad generates: for example, developing language skills, fostering cultural understanding and intercultural competence, facilitating personal growth and identity formation, and increasing career opportunities. Juxtaposing these alleged benefits with the themes that have emerged from the empirical studies reported in this special issue, this article critically examines the social imaginary of study abroad. Various factors that affect the outcomes of study abroad indicate that students' sojourn experiences and purported benefits do not have a simple causal relationship; rather, the relationship is fraught with complexities and contradictions. Despite potential rewards, study abroad cannot escape gender, racial, geographical and socioeconomic inequalities.